Guidance and Counseling Teachers' Efforts in Fulfilling the Developmental Tasks of Alpha Generation Students - Sabarrudin, Sabarrudin; Putri, Nadya; Nazhifah, Nada; Nami, Nelmi; Rahmadani, Anisa; Oktarini, Ira (International Journal of Research in Counseling, 2024)
Developmental tasks are a series of tasks that must be completed by a student/counselor at a certain stage of life/development. Developmental tasks arise from physical maturity, psychological maturity, social or cultural demands, and personal values and aspirations. When a student/counselor successfully completes a developmental task, the student or learner feels satisfied and becomes an asset to complete the next stage of developmental tasks. This study aims to determine the efforts of guidance and counseling teachers in fulfilling the developmental tasks of alpha generation students. The type of research used is qualitative literature research which is a literature study. The results revealed that the teacher's efforts in achieving the developmental tasks of alpha generation students or learners are as follows: Needs assessment, needs analysis, planning of services to be provided to students or learners, implementation of counseling, and others related to developmental issues, guidance of student services, evaluation, and reflection of services.